Social justice work as activism: The work of education professionals in England and Jamaica - Miller, Paul; Hill-Berry, Nola P.; Hylton-Fraser, Kadia; Powell, Shernette (My University, 2019)
“Social justice” is perhaps the most used word among educators in developed countries, and over the past decade, social justice work can be seen through, mostly government led initiatives and campaigns, aimed at promoting social inclusion, tolerance, respect, and reducing poverty, racism, class barriers, etc. Despite much talk about social justice, it is often unclear in any practical terms what is meant by ‘doing social justice’, hence the aim of this study to understand what it means for education professionals to foreground social justice in their work. This qualitative phenomenological study of education professionals in England and Jamaica (two university lecturers, a principal, and a secondary school teacher) sheds light on how educators in different educational contexts and national education systems conceptualise and undertake social justice work in their daily job roles. The guiding question was, “How do different education professionals do social justice work?” Despite national, cultural, institutional and role differences, education professionals conceived social justice as ‘doing right by others’, and working collaboratively was found to be key to successfully making changes and bringing about improvements. Furthermore, participants approached social justice work through pedagogic activism, emancipatory activism and regulatory activism.
Keywords: social justice; England; Jamaica; regulatory; pedagogic; emancipatory; activism